Triumph over abuse : healing, recovery, and purpose after an abusive relationship - Murray, Christine E. (New York, NY : Routledge, 2021)
"In this book Christine Murray carefully weaves her personal experiences as a survivor with her professional expertise as a counselor, community advocate, and researcher into a comprehensive guidebook for survivors of abuse. It offers extensive practical guidance on a range of topics, such as building coping skills, surrounding yourself with the right kinds of support, working through traumatic memories, and channeling your experience into helping others and making a difference in the world. The book will inspire and equip survivors of abuse to build full, meaningful lives despite the trauma they have faced, as well as being a tool for clinicians to use to support clients"--
Introduction: Triumphing Over Abuse -- Practicing Self-Care and Coping -- Surrounding Yourself with the Right Support -- Educating Yourself about Abuse -- Taking Back Control of Your Mind -- Fostering Positive Mental and Emotional Health -- Being the Best Parent You Can Be -- Dealing with Continued Abuse -- Building a Strong Foundation for Your Finances and Career -- Helping Others -- Telling Your Story, On Your Own Terms -- Conclusion: Beyond Survivorship.
OCLC-licensed vendor bibliographic record.
Keywords: Victims of family violence; Family violence; Intimate partner violence; PSYCHOLOGY / Psychotherapy / Couples & Family; PSYCHOLOGY / Psychotherapy / Counseling; SELF-HELP / Abuse